Assessments of productive performance, eggshell quality, excreta moisture, and incubation traits of laying breeder hens fed a proprietary blend of Quillaja and Yucca - Souza, Otoniel F.; Adams, Carine B.; Agilar, Jessica C.; Biselo, Valeria; Mello, Renius O.; Gomez, Luis G.; Bonaspetti, Sandra; Stefanello, Catarina (Frontiers in Veterinary Science, 2023)
A study was conducted to evaluate performance, eggshell quality, nutrient metabolizability, and incubation traits of laying breeder hens fed diets supplemented with an additive containing polyphenols and saponins of a proprietary blend from Quillaja saponaria and Yucca schidigera (QY) biomass. Hens were fed 4 feeds in 5 periods of 28 days each from 30 to 49 weeks of age. Experimental feeds were a Control diet; Control + virginiamycin (33 g/ton); Control + QY (250 g/ton) and Control + virginiamycin + QY. A total of 40 White Plymouth Rock and 44 Red Rhodes Island breeder hens were allocated in individual cages using a completely randomized block design with 21 replicates. Performance parameters, evaluated per period, were egg production, egg weight, FCR, egg mass, and culled eggs (eggs not suitable for incubation due to defects of the egg shell – cracked, broken or damaged eggs). All eggs were collected in the last 4 days of each period to evaluate specific egg weight, percentage of albumen, yolk and shell, and Haugh unit as well as cuticle quality, shell strength, and shell thickness. At the end of the experiment, nutrient metabolizability assessment and four incubations were conducted. There were no interactions between diet and period in all evaluated responses (P > 0.05). Experimental diets did not affect daily egg production, egg weight, and egg mass as well as Haugh unit, yolk and albumen percentage, and yolk color (P > 0.05). However, hens fed Control + QY produced eggs with better shell strength, shell thickness, and cuticle quality than hens fed the Control (P < 0.05). Hens fed Control + QY or Control + virginiamycin + QY had lower culled eggs, better FCR and higher egg specific weight, shell percentage, and yolk strength compared to breeder hens fed the Control (P < 0.05). In general, hens fed QY achieved enhanced performance and egg quality compared to virginiamycin. In conclusion, laying breeder hens fed diets supplemented with Quillaja and Yucca additive, from 30 to 49 weeks of age, maintained their productive performance, had improved eggshell and cuticle quality and reduced culled, dirty and contaminated eggs.